Social Responsibility Accounting Disclosure and its reflection on the financial performance of Islamic banks - Al- Sammarraee, Ammar Esam; Al- shareeda, Nadya Abduljabbar; Algasra, Rogaya Mansoor (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to demonstrate the extent of the commitment of Islamic banks / retail sector in the Kingdom of Bahrain to the Corporate social responsibility disclosure (CSRD) and its exercise of it, and the level of disclosure in its annual reports for the years 2014- 2018 and to determine the efficiency of the financial performance of Islamic banks researched in the Kingdom of Bahrain by extracting ratios finance through analyzing the data obtained from the annual financial reports of Islamic banks that is considered as the research sample. The next stage of the present research is comparing them with the average sectoral standard, and measuring the impact of the obligation to disclose social responsibility on the financial performance of Islamic banks in the Kingdom of Bahrain, and was used as long as the methodology of the analytical description is because it is the most appropriate with the goals and variables of the research, in addition to being consistent with the research hypothesis, the researcher used a model of social responsibility disclosure index and adopted the financial ratios as an indicator to measure the dependent variable (financial performance) through which the researcher was able to perform the analysis of the obtained data from a sample chosen from Islamic banks in the Kingdom of Bahrain. The results of the research found that Islamic banks in the retail sector in the Kingdom of Bahrain are committed to accounting disclosure for social responsibility in their annual reports, ranging between (65%- 85%), and Islamic banks were the highest commitment in accounting disclosure for social responsibility has achieved efficiency in financial performance. The rate of return on assets was better, although there is a general weakness in the financial performance of banks researched using the return on assets and this is due to the weak returns and revenues of Islamic banks from the Islamic financing tools used and the failure to reach the ratio of the average sectoral standard of the bank. The study recommends the necessity of increasing the levels of disclosure for social responsibility in its annual reports, increasing returns for those banks and raising the efficiency of financial performance for Islamic banks.